2022
DOI: 10.1002/cpp.2756
|View full text |Cite
|
Sign up to set email alerts
|

Self‐report measures of secure attachment in adulthood: A systematic review

Abstract: Background: Secure attachment in adulthood is associated with many markers of adaptive functioning. Valid and reliable self-report measures of attachment security could provide a practical tool to help advance strengths-based research and clinical work. Previous reviews have not specifically examined the psychometric properties of self-report instruments with respect to secure attachment or systematically appraised the methodological quality of relevant validation studies.Method: A systematic review was comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…Unfortunately, attachment measures have been developed using neurotypical populations, and their use in individuals with ASC, whether using interview or self-report, is problematic (Davis & Kramer, 2021) and could lead to inflated estimates of attachment insecurity in ED samples. Relatedly, whilst the attachment measures used by studies in this review were generally rated as having a low risk of bias, it should be noted that more in-depth reviews of the psychometric properties of attachment measures have identified multiple gaps in evidence for the adequacy of such properties (Jewell et al, 2019;Justo-Núñez et al, 2022). It is notable that no studies in the review assessed attachment beyond the individual's own account via interview or self-report.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Unfortunately, attachment measures have been developed using neurotypical populations, and their use in individuals with ASC, whether using interview or self-report, is problematic (Davis & Kramer, 2021) and could lead to inflated estimates of attachment insecurity in ED samples. Relatedly, whilst the attachment measures used by studies in this review were generally rated as having a low risk of bias, it should be noted that more in-depth reviews of the psychometric properties of attachment measures have identified multiple gaps in evidence for the adequacy of such properties (Jewell et al, 2019;Justo-Núñez et al, 2022). It is notable that no studies in the review assessed attachment beyond the individual's own account via interview or self-report.…”
Section: Discussionmentioning
confidence: 94%
“…Kenny & Hart (1992) and Datta et al (2021) both used measures that lacked evidence of convergent validity data with another attachment measure. Sommer et al (2021) used a German version of the Relationship Styles Questionnaire (Griffin & Bartholomew, 1994), a measure which yields scales that do not map clearly onto our four higher-order attachment constructs, and is known to have poor psychometric properties (Justo-Núñez et al, 2022). Finally, we excluded Lehoux & Howe's (2007) study comparing women with BN with their sisters as a control group from the metaanalysis, since it differed in methodology to all other studies.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Unfortunately, attachment measures have been developed using neurotypical populations, and their use in individuals with ASC, whether using interview or self‐report, is problematic (Davis & Kramer, 2021) and could lead to inflated estimates of attachment insecurity in ED samples. Relatedly, while the attachment measures used by studies in this review were generally rated as having a low risk of bias, it should be noted that more in‐depth reviews of the psychometric properties of attachment measures have identified multiple gaps in evidence for the adequacy of such properties (Jewell et al, 2019; Justo‐Núñez et al, 2022). It is notable that no studies in the review assessed attachment beyond the individual's own account via interview or self‐report.…”
Section: Discussionmentioning
confidence: 95%
“…Kenny and Hart (1992) and Datta et al (2021) both used measures that lacked evidence of convergent validity data with another attachment measure. Sommer et al (2021) used a German version of the Relationship Styles Questionnaire (Griffin & Bartholomew, 1994), a measure which yields scales that do not map clearly onto our four higher-order attachment constructs, and is known to have poor psychometric properties (Justo-Núñez et al, 2022). Finally, we excluded Lehoux and Howe's (2007) study comparing women with BN with their sisters as a control group from the meta-analysis, since it differed in methodology to all other studies.…”
Section: Narrative Synthesismentioning
confidence: 99%
“…Finally, adult attachment was assessed with a self-report scale [ 29 ]. Although this measure demonstrated excellent psychometric properties (see Justo-Núñez and colleagues [ 59 ] for a review), future research should replicate these results also using other instruments [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%